The Influence of Artificial Intelligence Utilization and Digital Personalization on Purchase Decisions through Consumer Trust as a Mediating Variable - Andri Catur Trissetianto; Eidelweijs AP; Hapzi Ali; Dedy Tri Cahyono; Jaja Miharja (Greenation Management and Business Review, 2025)
This study aims to analyze the influence of artificial intelligence utilization and digital personalization on purchase decisions through consumer trust as a mediating variable. Rapid digital transformation has encouraged e-commerce platforms to implement artificial intelligence-based systems to improve customer experience through product recommendations, personalized services, and predictive interactions. However, the effectiveness of these digital strategies in encouraging purchase decisions depends largely on consumer trust in digital systems. This research uses a quantitative approach with a survey method involving marketplace users who actively conduct online transactions. Data were collected through structured questionnaires distributed to respondents who have experience using digital marketplace platforms. The data analysis technique applies Partial Least Squares Structural Equation Modeling using SmartPLS. The results indicate that artificial intelligence utilization positively influences consumer trust, digital personalization positively affects consumer trust, and consumer trust significantly affects purchase decisions. Furthermore, consumer trust mediates the relationship between artificial intelligence utilization and digital personalization toward purchase decisions. These findings indicate that trust remains a strategic factor in strengthening digital business competitiveness in the current marketplace ecosystem.